The Role of Women in the Ministry of Jesus (A Study in the Gospel of Luke) - Nainggolan, Daniel Maniur; Salim, Tommy; Acung, Warkis; Nainggolan, Reynold (Journal of Social Science and Education Research, 2024)
This paper examines the pivotal role of women in the ministry of Jesus Christ, going beyond the often limited historical representation. A comprehensive analysis of the Gospel texts reveals the diverse roles women played, ranging from financial support and direct service to Jesus—such as Mary Magdalene, Joanna, and Salome, who remained faithfully by His side until His death and even participated in His burial—to their role as primary witnesses to His resurrection. These women were not merely passive recipients of Jesus' teachings but were active agents in the spread of the Gospel and the formation of the early Christian community. This study particularly highlights their courage, loyalty, and steadfast faith amidst the patriarchal culture of their time, demonstrating their significant contributions, which have often been overlooked in traditional narratives. Furthermore, the paper explores the theological implications of these women's roles, challenging interpretations that marginalize or underestimate their active participation in Jesus' life and ministry. Thus, this research calls for a more inclusive and balanced interpretation of the Gospel texts to rightly acknowledge the fundamental contributions of women in shaping the history and development of Christianity. It also encourages the continued participation of women in serving God today.